Challenging behaviour and epilepsy in patients with intellectual disability: frequency and mutual association - Muhammad Shakeel; Adeela (Journal of the Pakistan Medical Association, 2024)
Comorbid epilepsy and challenging behaviours is quiet common in patients with ID (intellectual disability). This study aims to determine the frequency and mutual association between epilepsy and challenging behaviours. In this cross-sectional analytical study, 252 patients were enrolled through convenient sampling technique. Comorbid epilepsy and CB (challenging behaviour) were seen in 111 (44.6%) and 116 (46.6%) patients, respectively. Epilepsy and severity of intellectual disability (ID) are statistically and significantly associated with challenging behaviour. This study concluded that comorbid epilepsy is more common among people with ID as compared to the general population. The clinical variables, i.e. comorbid epilepsy and severity of ID have statistically significant association with the CB. Keywords: Epilepsy, Challenging behaviour, Intellectual disability.